Fusaproliferin, Terpestacin and Their Derivatives Display Variable Allelopathic Activity Against Some Ascomycetous Fungi. Issue 11 (7th November 2016) - Cimmino, Alessio; Sarrocco, Sabrina; Masi, Marco; Diquattro, Stefania; Evidente, Marco; Vannacci, Giovanni; Evidente, Antonio
Abstract : Abstract : Herbivorous mammal dung supports a large variety of fimicolous fungi able to produce different bioactive secondary metabolites to compete with other organisms. Recently, the organic extracts of the Solid State Fermentation (SSF) cultures of Cleistothelebolus nipigonensis and Neogymnomyces virgineus, showing strong antifungal activity, were preliminarily investigated. This manuscript reports the isolation of the main metabolites identified, using spectroscopic and optical methods, as fusaproliferin (1 ) and terpestacin (2 ). Furthermore, some key hemisynthetic derivatives were prepared and their antifungal activity was tested against the same fungi previously reported to be affected by the organic extracts obtained from SSF. These metabolites and their derivatives resulted able to reduce the growth of Alternaria brassicicola, Botrytis cinerea and Fusarium graminearum in a variable extent strongly dependent from chemical modifications and test fungi. The hydroxy enolic group at C(17) appeared to be a structural feature important to impart activity. This study represents the first report of these secondary metabolites produced by C . nipigonensis and N . virgineus .